Analysis of The Needs of Local Government Information Systems in The Digital Era - Putri Balqis; Puji Aloina Br Ginting; Rara Dena Suganda; Meriana Buulolo; Sela Indriani; Galih Supraja (International Journal of Economic Research and Financial Accounting, 2025)
Digital transformation provides opportunities as well as challenges for local governments to improve efficiency, transparency, and quality of public services. This study aims to analyze the needs of the Regional Government Information System (SIPD) by approaching a literature review of 10 journals. The focus of the analysis includes three main aspects: information technology infrastructure, data security, and human resource (HR) capacity building. Based on the results of the study, there were 8 selected journals that showed significant contributions, while 2 journals were used as comparisons. The results of the study show that adequate infrastructure development, solid data security policies, and improvement of human resource competencies are the keys to the successful implementation of SIPD. This study recommends improving policy strategies to support the digitalization of local government and there is still a need for periodic evaluation and monitoring of information systems.